Clinician views of patient decisional conflict when deciding between dialysis and conservative management: Qualitative findings from the PAlliative Care in chronic Kidney diSease (PACKS) study. (December 2017) - Noble, Helen; Brazil, Kevin; Burns, Aine; Hallahan, Sarah; Normand, Charles; Roderick, Paul; Thompson, Colin; Maxwell, Peter; Yaqoob, Magdi
Background: Only a paucity of studies have addressed clinician perspectives on patient decisional conflict, in making complex decisions between dialysis and conservative management (renal supportive and palliative care). Aim: To explore clinician views on decisional conflict in patients with end-stage kidney disease. Design: Interpretive, qualitative study. Setting and participants: As part of the wider National Institute for Health Research, PAlliative Care in chronic Kidney diSease study, semi-structured interviews were conducted with clinicians (nephrologists n = 12; 7 female and clinical nurse specialists n = 15; 15 female) across 10 renal centres in the United Kingdom. Interviews took place between April 2015 and October 2016 and a thematic analysis of the interview data was undertaken. Results: Three major themes with associated subthemes were identified. The first, 'Frequent changing of mind regarding treatment options', revealed how patients frequently altered their treatment decisions, some refusing to make a decision until deterioration occurred. The second theme, 'Obligatory beneficence', included clinicians helping patients to make informed decisions where outcomes were uncertain. In weighing up risks and benefits, and the impact on patients, clinicians sometimes withheld information they thought might cause concern. Finally, 'Intricacy of the decision' uncovered clinicians' views on the momentous and brave decision to be made. They also acknowledged the risks associated with this complex decision in giving prognostic information which might be inaccurate. Limitations: Relies on interpretative description which uncovers constructed truths and does not include interviews with patients. Conclusion: Findings identify decisional conflict in patient decision-making and a tension between the prerequisite for shared decision-making and current clinical practice. Clinicians also face conflict when discussing treatment options due to uncertainty in equipoise between treatments and how much information should be shared. The findings are likely to resonate across countries outside the United Kingdom.